The Russian Oil and Gas Sector: Facing the New Challenges - Vasily Astrov (The Vienna Institute for International Economic Studies (wiiw), 2003)
Russian oil and gas are playing a vital role in the world markets, but they also represent an important and (still) the most successful part of the national economy. However, whether the oil and gas sector will become an engine for the country's development in the medium and long run depends to a large extent on the performance of the sector itself, and particularly on whether it will be able to overcome the looming supply bottlenecks. Part of the problem is to be solved via the large-scale energy-saving measures envisaged by the federal 'Energy Strategy' and implying, among other things, a tariff reform aimed at bringing domestic prices for natural gas and electricity closer to the world level. In addition, the country's gas industry is to be reorganized on a competitive basis, with only transportation and distribution remaining in state hands. In the oil sector, transportation constraints are becoming much of a concern, as they may hamper the country's ambitious projects of simultaneous penetration into several important energy markets, such as those of the United States and East Asia. As of now, there are reasons to believe that Russia will continue its strategy of free-riding on OPEC supply cuts in the years to come, not least because of the recent warming of the Russian-American relations. Another issue is whether the oil sector will be able cope with production bottlenecks, as the bulk of currently operating deposits are largely exhausted and the most promising oilfields are situated in remote areas of Northern Russia, East Siberia and the Far East. Finally, a lot will depend on whether Russian exporters will be able to export more refined oil products and less crude oil.
Keywords: Q4; L7; O5; 330